Analisis Pengaruh Sistem Pengendalian Internal (SPI), Kompetensi Pemerintah Desa, Aksesibilitas Laporan Keuangan Dan Transparansi Terhadap Akuntabilitas Pengelolaan Dana Desa Di Kabupaten Kendal - Nurkholik .; Febriyanti . (Jurnal Ekonomika dan Bisnis, 2022)
This study aims to examine the effect of the internal control system, village government competence, accessibility of financial and transparency of village fund management accountability. The dependent variable in this study is village fund management accountability and the independent variable in this study is the internal control system, village government competence, accessibility of financial and transparency. The population used in this study is the village government in Kendal Regency. The data collection technique used is primary data through the distribution of questionnaires with a sample of 73 respondents with the village head as the respondent. The sampling method in this study is propotional random samping. The data analysis method used is the use of data quality, classical assumption testing, multiple linear regression analysis and hypothesis testing. The result of data analysis in this study indicate that the internal control system, village government competence, accessibility of financial and transparency have a significant effect on village fund management accountability. The coefficient of determination (R2) in this study is 55,8% while the rest is explained by other variable outside of this study.